Ischaemic neuropathy of the lumbosacral plexus following intragluteal injection. Issue 6 (June 1980) - Stöhr, M; Dichgans, J; Dörstelmann,
Abstract : A lesion of the lumbo sacral plexus may result from an inadvertent intra-arterial injection of vasotoxic drugs into one of the gluteal arteries. Symptoms and follow-up of three cases are reported. The neuropathy is attributed to a toxic endarteritis with retrograde propagation of spasm and thrombosis. Swelling an bluish discoloration of the buttocks ("embolia cutis medicamentosa") as well as an impaired circulation in the homolateral leg are associated with the neurological syndrome in fully developed cases and makes possible a correct diagnosis.